Pengaruh Sertifikasi, Kualitas Kehidupan Kerja dan Kompetensi Profesional Terhadap Kinerja Guru di SMP Negeri Se-Kecamatan Selesai Kabupaten Langkat - Siti Armina; Elfrianto Elfrianto; Faisal Rahman Dongoran (EDUTECH, 2023)
The purpose of this study was to determine the effect of teacher certification, quality of work life and professional competence on teacher performance in public junior high schools in the Selesai sub-district of Langkat Regency. This research was conducted at public Junior High School in the Selesai Sub-District of Langkat Regency with a sample size of 70 people. Data collection techniques using questionnaires and data analysis techniques namely validity, reliability, t test and F test. The results showed that there was an effect of teacher certification on teacher performance where the t value obtained was 2,220 with the acquisition of a Sig value of 0.030 0.05 and the results of simple regression analysis Y = 0,127 + 0,234X1, which means that every increase in one certification value will be followed by an increase in performance value of 0,234. There is an effect of quality of work life on teacher performance where t count is 5,948, with the acquisition of Sig 0.000 0.05 and the results of regression analysis Y = 0,127 + 0,598X2, which means that every increase of one value of quality of work life will be followed by an increase in performance value of 0,127. There is an effect of professional competence on teacher performance where t count is 2,132, with the acquisition of Sig 0,037 0,05 and the results of regression analysis Y = 0,127 + 0,145X3, which means that every increase in one value of professional competence will be followed by an increase in teacher performance value of 0,145. There is an effect of certification (X1), quality of work life (X2) and professional competence (X3) together on teacher performance where the F value is 41,425 and the Sig value is 0.000. The amount of influence is shown by the coefficient of determination R2 (R square) = 0,653 which means that certification (X1), quality of work life (X2) and professional competence (X3) together have an influence on teacher performance by 65,3% and the remaining 34,7% is determined by other factors. The results of multiple linear regression analysis show the equation Y = 0,127 + 0,234X1 + 0,598X2 + 0,145X3